Case Report: Effective management of residual glioblastoma with combined modality therapy - Chang, Heng-Jui; Ke, Chiao-Hsu; Wang, Yu-Shan; Kuo, Yu-Cheng (Frontiers in Oncology, 2025)
Glioblastoma (GBM) is an aggressive primary brain tumor with a poor prognosis, often characterized by rapid progression and resistance to conventional therapies. This case report discusses the comprehensive management of a 60-year-old female diagnosed with residual GBM following initial surgical intervention. The treatment regimen included craniectomy, concurrent chemoradiotherapy (CCRT), adjuvant temozolomide, and weekly sessions of modulated electro-hyperthermia (mEHT, Oncothermia). Remarkably, the patient exhibited significant tumor shrinkage, improved neurological symptoms, and an extended survival period compared to typical outcomes. mEHT was utilized to enhance the efficacy of chemoradiotherapy and temozolomide by selectively targeting cancer cells and improving drug delivery. Integrating mEHT into the standard treatment protocol appears to have contributed to better therapeutic outcomes and improved quality of life for the patient. This case underscores the potential benefits of incorporating mEHT into multimodal treatment strategies for GBM, highlighting its role in enhancing the effects of conventional therapies. Future research and clinical trials are warranted to further explore the synergistic effects of mEHT with standard GBM treatments, aiming to establish more effective protocols and improve overall patient survival and quality of life. This report adds to the growing body of evidence supporting the use of innovative, integrative approaches in the management of aggressive brain tumors like GBM.